Business associations in Kenya: the success factors. Issue 2 (2nd July 2015) - Irwin, David; Githinji, Mary
Abstract : Governments create the political and economic environment in which their countries' businesses operate, usually described as the 'enabling environment' or 'investment climate'. In response, business associations seek to influence public policy to make it easier for their members to "do business". Scholars suggest that interest groups are able to form lasting relationships with governments based on a resource exchange mechanism. This paper suggests that, at least in developing countries, a more nuanced explanation is necessary. Business associations, in particular, need proactively to pursue a logic of 'competence' as well as a logic of 'positive relationships'. This paper assesses the outcomes of advocacy projects undertaken by business associations in Kenya in the period 2008–2013, considers the degree to which the associations contributed to the decision to change policy and then analyses the factors perceived by business associations to have led to their success in influencing public policy. We find evidence to support the expectation that business associations must develop a wide range of competences whilst building relationships with multiple stakeholders. The findings will be relevant to practitioners as well as to researchers and donors. Copyright © 2015 John Wiley & Sons, Ltd.